Development of Conductivity of Acrylic Polymer Using Ionic Liquids Incorporated with Zinc Oxide Nanoparticles. Issue 18 (12th December 2017) - Seki, Yasemin; Seki, Yoldaş
ABSTRACT: In this study, we synthesized antistatic and ultraviolet-resistant acrylic films with a combination of ionic liquids and ZnO nanoparticles for the prevention of static electricity and ultraviolet instability. ZnO and two different ionic liquids such as 1-ethyl-2, 3-dimethylimidazolium ethyl sulfate and methyl-tri- n -butylammonium methylsulfate were preferred to achieve conductive and ultraviolet-resistant acrylic films. To obtain the highest ultraviolet protection factor and the lowest surface resistivity for the acrylic film, the combined effect of ZnO nanoparticles and the ionic liquids was utilized. The surface resistivity, thermal conductivity and effusivity, thermogravimetric analysis, and ultraviolet resistivity of the films were investigated. Surface morphology of the films and distribution of ZnO were also observed by scanning electron microscopy. The acrylic polymer exhibits higher ultraviolet resistance and lower transmission even in the low content of ZnO nanoparticles as compared with the neat polymer. The film consisting of methyl-tri- n -butylammonium methylsulfate ionic liquid showed the highest electrical conductivity performance even after 150 days. Consequently, ZnO nanoparticles are determined to be influential on ultraviolet-resistant properties, whereas ionic liquids are efficient on electrical conductivity performance of the acrylic polymer. GRAPHICAL ABSTRACT: